The Effect of Ownership of Managerial, Independent Board of Commissioners, Board of Directors and Intellectual Capital on Financial Performance - Eva Dwi Rahmawati; Sri Wahyuni; Novi Dirgantari; Dwi Winarni (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2022)
Financial performance is one of the significant aspects of measuring industrial profits. The purpose of this research is to find empirical evidence of the influence of Managerial Ownership, Independent Board of Commissioners, Board of Directors, and Intellectual Capital on Financial Performance. The population in this study are banking companies in 2018-2021 listed on the Indonesia Stock Exchange (IDX). The sampling technique used is a purposive sampling technique to obtain a sample of 79 samples that have met the criteria. The data analysis technique used is multiple regression analysis. Financial performance in this study was measured using the profitability ratio (ROA). The results of this study prove that the variables of managerial ownership, independent board of commissioners, and board of directors do not affect financial performance. While the intellectual capital variable has a positive effect on financial performance.